2018
DOI: 10.1097/id.0000000000000707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Short Drilling Implant Protocol on Osteotomy Site Temperature and Drill Torque

Abstract: Within the limitations of the study, the short drilling protocol proposed herein may represent a safe approach for implant site preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Bratu et al and Mihali et al suggested the use of a short drilling implant protocol (sdip) during implant osteotomy preparations, supporting the significantly reduced duration [ 56 , 57 ]. The sdip consisted only of the use of the pilot drill and the final drill.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bratu et al and Mihali et al suggested the use of a short drilling implant protocol (sdip) during implant osteotomy preparations, supporting the significantly reduced duration [ 56 , 57 ]. The sdip consisted only of the use of the pilot drill and the final drill.…”
Section: Discussionmentioning
confidence: 99%
“…The sdip consisted only of the use of the pilot drill and the final drill. Compared to the conventional protocol, the sdip did not show any statistically significant difference in temperature increase and drilling torque [ 56 ]. In addition, there was no statistically significant difference on bone remodeling between the conventional and sdip 12 months after epicrestal implant placement, both showing around 1 mm of crestal bone loss [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that when the perforation required for implant placement is less invasive, there is a potential reduction in peri-implant bone inflammation [10]. Narrow implants required a reduced drilling protocol; in consequence, it might help to improve osteoblast functioning, reduce swelling and bone loss [11] in patients where the inflammation is already set and playing a relevant role in the pathogenesis of the T2DM, now redefined as an immune disorder [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined insertion speed [7,13,14]. Studies on speed generally focused on the effects of predrilled holes on temperature [20]. Several studies examined the effect of drilling speed in pre-drilled holes on subsequent implant stability [21,22].…”
Section: Introductionmentioning
confidence: 99%